2017
DOI: 10.17957/tpmj/17.3631
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome; Agreement Between Metabolic Syndrome Diagnostic Criteria Among Type 2 Diabetes Mellitus Patients

Abstract: ABSTRACT… Background: Metabolic syndrome and diabetes mellitus are the modifiable risk factors of cardiovascular diseases that double the chance of illness when occur together. Little work has been reported on the superlative criteria to diagnose metabolic syndrome among diabetics from the country. Therefore, the study was aimed to find the agreement between metabolic syndrome diagnostic criteria among type 2 diabetics. Methods: The retrospective data of 373 known type 2 diabetics who had reported history of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…The agreement of these criteria as shown by the κ statistics was 0.751 (p < 0.001). Previous studies also reported a good agreement between the WHO and ATP criteria,7,17,18 with a κ statistic of 0.56 in one report 17. In another hospital-based study that included 373 known cases of T2DM,18 investigators found good agreement between the WHO and ATP III criteria ( κ = 0.366; P < 0.001).…”
Section: Discussionmentioning
confidence: 79%
“…The agreement of these criteria as shown by the κ statistics was 0.751 (p < 0.001). Previous studies also reported a good agreement between the WHO and ATP criteria,7,17,18 with a κ statistic of 0.56 in one report 17. In another hospital-based study that included 373 known cases of T2DM,18 investigators found good agreement between the WHO and ATP III criteria ( κ = 0.366; P < 0.001).…”
Section: Discussionmentioning
confidence: 79%
“…In the present study, overall rate of HTN 58.1% exhibit that HTN was a common comorbid condition of T2DM in the settings. Although, it was equivalent to 59.5% HTN observed in Ethiopian diabetics 9 , but was markedly lower than of 70.5% 10 and 74.0% 11 in Pakistani diabetics, 72.4% in Jordanian diabetics 8 , 79.4% in Spanish diabetics 12 , and 83.4% in Emirati diabetics. 13 The previously undiagnosed HTN 25.3% suggesting that every 4 th diabetic remain with undiagnosed HTN in the settings was lower than 37.4% undiagnosed HTN in Spanish diabetics 12 , but three times higher than 7.0% in Jordanian diabetics.…”
Section: Discussionmentioning
confidence: 60%
“…(17)(18)(19) A concordância substancial entre os critérios da IDF e do NCEP-ATPIII dos nossos achados apoia o que tem sido evidenciado na literatura em estudos com PVHIV e outros grupos. (9,(19)(20)(21) O resultado dessa concordância implica que esses critérios podem classificar o mes-mo indivíduo com SM, o que pode ser justificado pela utilização de quatro componentes metabólicos com o mesmo parâmetro de referência. A divergência dos critérios está na CA, que possui ponto de corte diferente, no critério da IDF é menor, comparado ao do NCEP-ATPIII.…”
Section: Discussionunclassified